a COMPARATIVE STUDY ON DEDUCTIVE VS INDUCTIVE APPROACH IN TEACHING REPORTED SPEECH - rosida, ana (Study Program of English Literature, 2018)
This research was conducted to find out and to compare the effectiveness of teaching reported speech for the second semester students of English Language and Literature Department of Adab and Humanity Faculty in Alauddin State Islamic University Makassar between deductive and inductive approaches. The research employed quasi experimental design. The subjects consisted of 36 students which divided into two groups; 18 students in deductive group and 18 in inductive group. The researcher used a test of reported speech both in deductive and inductive groups. The data obtained through the test were analyzed by using inferential statistics through SPSS version 15.0 program. In conducting the research, the researcher applied deductive approach for Ag. 1 class and inductive approach for Ag. 2 class to improve the students’ reported speech mastery. The research result showed that there was an improvement on the students’ reported speech mastery between pretest and posttest to both groups after the treatment. However, inductive approach was more significant than deductive approach. It is concluded that inductive approach gave better contribution to improve the students’ reported speech mastery. It was proven by the result of inferential statistics in testing the students’ score either in pretest or in posttest. Based on the result of the data analysis, there was a significant difference between the results of posttests of Ag. 1 and Ag. 2 classes, however deductive and inductive approaches showed the improvement well, inductive approach shows greater achievement than deductive (88.7778 < 81.2778). The final score of probability value in reported speech was lower than α (.039< 0.05). In other words, H1 and H2 were accepted and H0 was rejected. But to compare the effectiveness, H2 is accepted and H0 was rejected.